Application of Solid Dispersion Technology to Obtain a Model of Injectable Dosage Form of Indolocarbazole Derivative - A. P. Kolpaksidi; M. V. Dmitrieva; O. L. Orlova; L. V. Ektova; I. I. Krasniuk (Разработка и регистрация лекарственных средств)
Introduction. N. N. Blokhin National Medical Research Center of Oncology of the Ministry of Health of Russia synthesized an original derivative of indolocarbazole with the carbohydrate residue xylose, which has a pronounced cytotoxic and anti-angiogenic activity. The substance LCS-1269 is an amorphous powder that is almost insoluble in water, which causes difficulties in the development of an injectable dosage form (IDP). To solve this problem, a technological approach to obtain a solid dispersion (SD) of LCS-1269 has been proposed.Aim. To develop a model of IDP of the indolocarbazole derivative LCS-1269 based on SD.Materials and methods. We used a substance LCS-1269 synthesized in the Chemical Synthesis Laboratory of the N. N. Blokhin National Medical Research Center of Oncology. Emuxol 268, Kolliphor® P 188, Soluplus®, Lutrol® F68, Kollidon® 12 and Kollidon® 17, soybean phosphatidylcholine unsaturated S PC and saturated S PC-3 were investigated as carriers of the active substance. SD LCS-1269 was obtained by solvent removal: the active substance was dissolved in acetone, the carrier − in chloroform, the obtained solutions were mixed, transferred into a bottle and evaporated under vacuum (50 ± 5 mbar) in the desiccator at water bath temperature 65 ± 2 °С. To obtain aqueous solution of LCS-1269 dry mass was dissolved using different auxiliary substances or their mixtures: water for injection, ethanol 95 %, benzyl alcohol, Kollisolv® PEG 400, MONTANOX™ 80. To increase stability, the aqueous solution of LCS-1269 was lyophilized in an Edwards Minifast DO.2 freeze dryer.Results and discussion. Kollidon® 17 was chosen as the carrier material for the SD active substance. It was found that a clear solution of LCS-1269 with the concentration of the active substance 0.5 % was formed by dissolving the SD in ethanol 95 % and then gradually diluting the alcohol mixture with water for injection. In this case, the mass ratio of the components of the developed model IDF LCS : Kollidon® 17 : ethanol : water is 1 : 40 : 32 : 127. As a result of freeze-drying of the water-ethanol solution of LCS-1269 the IDF in the form of lyophilizate easily soluble in a 10 % solution of ethanol was obtained.Conclusion. An IDF model of the hydrophobic derivative of indolocarbazole LCS-1269 based on SD was developed and submitted for biological studies to evaluate its effectiveness.